2016
DOI: 10.5897/ajb2016.15405
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hypochlorite sterilization of culture medium in micropropagation of Gerbera hybrida cv. Essandre

Abstract: Micropropagation requires controlling contamination that might compromise the success of the process. Thermal sterilization is traditionally used; however, costs deriving from equipment acquisition and maintenance render this technique costly. With the purpose of finding an alternative to thermal sterilization, this research aimed at assessing the efficiency and ideal concentration of sodium hypochlorite for sterilization of culture media and glassware used during rooting of micropropagated Gerbera hybrida cv.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…At low active chlorine concentrations (up to 0.005%), sodium hypochlorite has proven viable in controlling bacterial manifestation in in vitro cultures of Eucalyptus benthamii at the establishment phase [16], Eucalyptus pellita at the multiplication phase [22], Sequoia sempervirens L. [21], the hybrid Gerbera hybrida cv. Essandre [24], Cochlospermum regium [25] and Bambusa vulgaris [26]. Our results for Eucalyptus mycrocoris agree with the literature: sodium hypochlorite at 0.003% produced the best response by eliminating microbial manifestations in 25% of individual 2 explants and 5% of individual 1 explants.…”
Section: Reduction Of Microbial Manifestationsupporting
confidence: 89%
“…At low active chlorine concentrations (up to 0.005%), sodium hypochlorite has proven viable in controlling bacterial manifestation in in vitro cultures of Eucalyptus benthamii at the establishment phase [16], Eucalyptus pellita at the multiplication phase [22], Sequoia sempervirens L. [21], the hybrid Gerbera hybrida cv. Essandre [24], Cochlospermum regium [25] and Bambusa vulgaris [26]. Our results for Eucalyptus mycrocoris agree with the literature: sodium hypochlorite at 0.003% produced the best response by eliminating microbial manifestations in 25% of individual 2 explants and 5% of individual 1 explants.…”
Section: Reduction Of Microbial Manifestationsupporting
confidence: 89%
“…Clorox ® , a conventional bleach that consists of 5.25% of sodium hypochlorite (NaOCl), has the ability to penetrate the inner layers of the plant. It has been extensively used along with ethanol as an effective surface sterilizing agent in various plant species such as Ludisia discolour [41], Gerbera hybrida [42], Ananas comosus [43], Jatropha curcas [44], Aquilaria malaccensis [45], sour cherry [46] and Taraxacum belorussicum [47].…”
Section: Discussionmentioning
confidence: 99%
“…As low as 12.6 μM aqueous CD was capable of sterilizing potato culture media. This concentration was lower than the concentration of sodium hypochlorite (NaOCl) used to sterilize media in previous studies 17,18,31 , but similar to the CD concentrations used in other plant species 1316 . Another advantage of using CD for sterilization is the low cost; the prices of sodium chlorite and food grade hydrochloric acid are far lower than commercial sodium hypochlorite products 11 .…”
Section: Discussionmentioning
confidence: 47%
“…The similar morphological features and rates of microtuber induction between autoclaved and CD sterilized media are in line with previous studies including Paris et al . 18 , while Teixeira et al . 17 and Cardoso & Silva 14 who reported that CD containing medium promoted the growth of plants.…”
Section: Discussionmentioning
confidence: 99%